Diversecity For Humanity And Sustainable Growth - Aziz, Azim A (MAJ - Malaysia Architectural Journal, 2025)
By 2050 the United Nation predicted 65% - 70% of the population will live in urban areas. By then, the world population will be approximately 9.8 billion people a 33% increase from 8 billion in 2023. However, most of the population growth will come from developing countries such as Africa and South Asia and at the same time, the population of many developed countries will decline. This study seeks to identify the effects of population density in cities in developed and developing countries and the need to design cities to be sustainable based on past, present and future cities’ data. Furthermore, large scale new future cities are introduced as a “solutions” to solve aliments besieging present day cities. The objective is to seek a set of guidelines to be considered wherever new cities or its conurbation are being designed.